Організація і методика аудиту та аналізу необоротних активів підприємства - Перев'язко, Анастасія Сергіївна (Ірпінь, 2025)
Автор оцінив динаміку встановлення теоретико-методичних аспектів обліку, аудиту та аналізу необоротних активів підприємства, дослідження практичних засад обліку, аудиту та аналізу ПрАТ «Вімм-Білль-Данн Україна». Досліджено сутність необоротних активів підприємства та проаналізувати існуючі наукові публікації щодо них; проаналізовано нормативне забезпечення національного законодавства з питань регулювання процесів обліку, аудиту та аналізу необоротних активів; проведено діагностику загально-економічного стану ПрАТ «Вімм-Білль Данн Україна» за 2021-2023 рр.; досліджено організацію та методику облік необоротних активів в компанії «Вімм-Білль-Данн Україна».

The author assessed the dynamics of establishing theoretical and methodological aspects of accounting, auditing and analysis of non-current assets of the enterprise, research into the practical principles of accounting, auditing and analysis of PrJSC "Wim-Bill-Dann Ukraine". The essence of the enterprise's non-current assets was studied and existing scientific publications on them were analyzed; the regulatory framework of national legislation on the regulation of accounting, auditing and analysis of non-current assets was analyzed; a diagnosis of the general economic condition of PrJSC "Wim-Bill-Dann Ukraine" was carried out for 2021-2023; the organization and methodology of accounting for non-current assets in the company "Wim-Bill-Dann Ukraine" were studied.
Keywords: необоротні активи; облік; аудит; аналіз; облікова політика; ефективність використання; первинні документи; коефіцієнтий аналіз; робочі документи; аудиторський звіт; non-current assets; accounting; audit; analysis; accounting policy; efficiency of use; primary documents; ratio analysis; working papers; audit report